Nickel alloy surface composite coating and preparation method thereof

By preparing a Ta diffusion barrier layer on the surface of the nickel alloy and alternately setting up the TiAlTa/(TiAlTa)xC1-x functional layer to form a composite coating, the wear and corrosion problems of nickel alloy under harsh conditions are solved, and the effects of high wear and corrosion resistance are achieved.

CN119553235APending Publication Date: 2025-03-04XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411721766.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Nickel alloys are easily worn or eroded under harsh conditions such as high-speed friction, high-temperature corrosion, or strong acids and alkalis, resulting in reduced performance and shortened service life. Existing coating materials and technologies are difficult to meet the wear and corrosion resistance requirements of nickel alloy components at the same time.

Method used

Ta is used as the diffusion barrier layer, and TiAlTa/(TiAlTa)xC1-x functional layer is alternately provided on its surface to form a multi-layer alternating structure of nickel alloy surface composite coating.

Benefits of technology

It effectively improves the resistance of the surface of nickel alloy to high temperature, corrosion and friction, enhances the bonding force between the coating and the substrate, and significantly extends the service life of nickel alloy components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553235A_ABST
    Figure CN119553235A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a nickel alloy surface composite coating and a preparation method thereof, and relates to the technical field of protective coatings, the nickel alloy surface composite coating comprises a Ta diffusion barrier layer prepared on the nickel alloy surface, and TiAlTa / (TiAlTa) xC1-x functional layers alternately arranged on the surface of the Ta diffusion barrier layer. The Ta diffusion barrier layer is adopted, so that excellent corrosion resistance is provided, corrosion of various corrosive media including strong acid, strong alkali and the like can be effectively resisted, the mutual diffusion effect of the nickel alloy and Ti, Al and other elements in the coating under the high-temperature condition is remarkably reduced, and the binding force of the coating and a base material is remarkably enhanced. The TiAlTa / (TiAlTa) xC1-x functional layers are alternately arranged, a formed multi-layer alternate structure can break the growth of penetrative columnar crystals and reduce the porosity, so that the corrosion resistance of the coating is improved, the surface layer (TiAlTa) xC1-x comprises various MAX phases and carbide phases, and the antifriction and wear-resistant effects and the corrosion resistance of the composite coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosed embodiments relate to the technical field of protective coatings, and in particular, to a nickel alloy surface composite coating and a preparation method thereof. Background Art

[0002] Nickel and its alloys are widely used in aerospace, transportation, food equipment, petrochemical and nuclear power generation due to their high strength, good heat resistance and excellent oxidation resistance. However, in some extreme or specific application environments, these properties may still not be sufficient to meet the needs of long-term stable operation. For example, under harsh conditions such as high-speed friction, high-temperature corrosion, or strong acids and alkalis, the surface of nickel alloys may be worn or corroded, which in turn affects their overall performance and service life.

[0003] Coating protection is one of the key ways to improve the service life of component materials. Transition metal elements such as Al, Cr, Ti, etc. are widely used in surface protective coatings of various component materials due to their excellent antioxidant and corrosion resistance. However, elements such as Al, Cr, Ti, etc. are easy to diffuse with nickel alloys under high temperature environments, resulting in the formation of various brittle intermetallic compounds at the interface between the coating and the substrate, making it easy to crack under external loads. Metal coatings usually have lower hardness and higher plasticity, which makes them more susceptible to scratches, wear and deformation when subjected to friction and wear. It can be seen that coating materials with a single component and structure and traditional preparation technologies are difficult to simultaneously meet the wear resistance and corrosion resistance requirements of nickel alloy parts in complex working conditions. Summary of the invention

[0004] The purpose of the present disclosure is to provide a nickel alloy surface composite coating and a method for preparing the nickel alloy surface composite coating, thereby overcoming the problem of poor coating performance caused by the limitations and defects of the relevant technology at least to a certain extent.

[0005] According to one aspect of the present disclosure, a nickel alloy surface composite coating is provided, wherein the nickel alloy surface composite coating comprises a Ta diffusion barrier layer prepared on the surface of the nickel alloy, and TiAlTa / (TiAlTa) x C 1-x Functional layer.

[0006] In an exemplary embodiment of the present disclosure, the TiAlTa / (TiAlTa) x C 1-x The total number of functional layers is 12 to 24 layers, and the TiAlTa / (TiAlTa) x C 1-x TiAlTa layer in the functional layer and (TiAlTa) x C 1-xThe modulation ratio of the layer is 1:1 to 1:3, and the TiAlTa / (TiAlTa) x C 1-x The outermost layer of the functional layer is (TiAlTa) x C 1-x The total thickness of the composite coating is 2 to 6 μm.

[0007] In an exemplary embodiment of the present disclosure, the purity of the Ta diffusion barrier layer is not less than 99%, and the thickness of the Ta diffusion barrier layer is 200-1000 nm.

[0008] In an exemplary embodiment of the present disclosure, the TiAlTa / (TiAlTa) x C 1-x The single layer thickness of the TiAlTa layer in the functional layer is 80-200nm; the TiAlTa layer is composed of the following components in atomic percentage: 40%-55% Ti, 30%-40% Al and 5%-25% Ta.

[0009] In an exemplary embodiment of the present disclosure, the (TiAlTa) x C 1-x In the layer, x satisfies 0.3≤x≤0.6, and the (TiAlTa) x C 1-x The single layer thickness of the layer is 80 to 400 nm, and the (TiAlTa) x C 1-x The phases contained in the layer include a ceramic phase and an amorphous carbon phase; the ceramic phase is X a Y b Z c C (X, Y, Z = Ti, Al, Ta, a + b + c = 1) ceramic phase.

[0010] According to one aspect of the present disclosure, a method for preparing a composite coating on a nickel alloy surface is provided, which is used to prepare the composite coating on the nickel alloy surface as described in any one of the above, comprising:

[0011] Fixing a TiAl target source and a Ta target source on a target holder of a vacuum chamber of a magnetron sputtering device, placing a nickel alloy substrate into the chamber and fixing it on a base, and evacuating the chamber until the vacuum degree reaches a first vacuum degree;

[0012] Argon gas is introduced into the vacuum chamber and the vacuum degree is maintained at a second vacuum degree, a bias power supply is turned on to perform ion cleaning on the surface of the nickel alloy substrate, and a TiAl target source and a Ta target source are turned on to bombard the nickel alloy substrate to obtain a nickel alloy substrate after bombardment and cleaning;

[0013] The flow rate of argon gas is adjusted to maintain the vacuum degree at the second vacuum degree, and a Ta target source is turned on to plate a Ta diffusion barrier layer on the surface of the nickel alloy substrate after bombardment cleaning;

[0014] Turning on the TiAl target source to deposit a TiAlTa layer on the surface of the formed Ta diffusion barrier layer;

[0015] In the vacuum chamber equipped with the TiAlTa substrate, C 2 H 2 / Ar mixed gas, prepared on the surface of TiAlTa layer (TiAlTa) x C 1-x layer;

[0016] In (TiAlTa) x C 1-x The surface of the layer is alternately prepared TiAlTa / (TiAlTa) x C 1-x Functional layer, including Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Composite coating on nickel alloy surface with functional layer.

[0017] In an exemplary embodiment of the present disclosure, the distance between the nickel alloy substrate and the TiAl target source and the Ta target source is 50-100 mm, and the first vacuum degree is 5.0×10- 3 ~5.0×10- 4 Pa, the deposition temperature of magnetron sputtering is 250~400℃.

[0018] In an exemplary embodiment of the present disclosure, in the step of ion cleaning, the negative bias voltage of the bias power supply is -600 to -800 V, and the duty cycle is 60% to 80%; the ion cleaning time is 10 to 25 minutes, the arc target power of the TiAl target source and the Ta target source is 100 to 150 W, and the bombardment time is 3 to 5 minutes.

[0019] In an exemplary embodiment of the present disclosure, when the Ta target source is turned on, the arc target power of the Ta target source is 100-150W, the negative bias voltage of the bias power supply is -80--120V, the duty cycle is 40%-60%, the deposition time is 10-60min, and the thickness of the Ta diffusion barrier layer is 200-1000nm; when the TiAl target source is turned on, the vacuum degree, the arc target power, the negative bias voltage, and the duty cycle of the Ta target source are the same as the vacuum degree, the arc target power, the negative bias voltage, and the duty cycle of the Ta target source when the Ta target source is turned on, the arc target power of the TiAl target source is 100-150W, and the deposition time is 2-5min.

[0020] In an exemplary embodiment of the present disclosure, in a vacuum chamber equipped with a TiAlTa layer substrate, C is introduced into the vacuum chamber. 2 H 2 / Ar mixed gas, prepared on the surface of TiAlTa layer (TiAlTa) x C 1-x Layers, including:

[0021] Keep the arc target power, negative bias voltage and duty cycle of TiAl target source and Ta target source unchanged, and introduce C 2 H 2 / Ar mixed gas, and maintain the vacuum degree at the third vacuum degree, the deposition time is 2 to 15 minutes, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x layer.

[0022] In the technical solution provided in the embodiments of the present disclosure, on the one hand, the use of Ta as a diffusion barrier layer not only provides excellent corrosion resistance and can effectively resist the erosion of various corrosive media including strong acids and strong alkalis, but also significantly reduces the mutual diffusion effect of elements such as Ti and Al in the nickel alloy and the coating under high temperature conditions, effectively avoiding the problem of brittle intermetallic compounds that are easily generated at the interface between the traditional Cr and Ti-based coatings and the Ni substrate, and significantly enhancing the bonding force between the coating and the substrate. On the other hand, by alternately setting TiAlTa / (TiAlTa) x C 1-x Functional layer, the multi-layer alternating structure formed can interrupt the growth of penetrating columnar crystals, reduce porosity, and thus improve the corrosion resistance of the coating. x C 1-x The inclusion of various MAX phases and carbide phases also provides the coating with good friction reduction and wear resistance. On the other hand, by precisely controlling the TiAlTa / (TiAlTa) x C 1-x The elemental composition ratio of the functional layer, combined with the modulation period design and preparation process optimization of the functional layer, effectively inhibited the continuous growth of columnar crystals, and successfully prepared a highly dense near-equiaxed crystal structure coating, which effectively prevented the rapid diffusion of corrosive media along the grain boundaries, thereby improving the corrosion resistance of the composite coating.

[0023] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0025] Figure 1 Schematic diagram of the structure of the composite coating on the surface of the nickel alloy in the embodiment of the present disclosure.

[0026] Figure 2 The flowchart of the method for preparing the composite coating on the surface of the nickel alloy in the embodiment of the present disclosure is schematically shown.

[0027] Figure 3 This is a SEM morphology image of the composite coating prepared on the surface of the Inconel 750 substrate in Example 1.

[0028] Figure 4 This is a profile data diagram of the wear scar cross section of the composite coating prepared on the surface of the Inconel 600 substrate in Example 2 after the wear resistance test.

[0029] Figure 5 This is the macroscopic morphology of the composite coating prepared on the surface of the pure nickel substrate in Example 3 after being subjected to 800°C high-temperature atmospheric oxidation experiment for 3 hours.

[0030] Figure 6 This is a SEM surface morphology of the composite coating prepared on the surface of the pure nickel substrate in Example 3 after being subjected to 800°C high-temperature atmospheric oxidation experiment for 3 hours.

[0031] Figure 7 This is a polarization curve of the corrosion performance of the composite coating prepared on the surface of the Inconel 718 substrate in Example 4 in concentrated nitric acid (6 mol / L) at 95°C. DETAILED DESCRIPTION

[0032] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0033] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0034] Coating protection is one of the key ways to improve the service life of component materials. Transition metal elements such as Al, Cr, and Ti are widely used in surface protective coatings of various component materials due to their excellent antioxidant and corrosion resistance. However, elements such as Al, Cr, and Ti are easy to diffuse with nickel alloys under high temperature environments, resulting in the formation of various brittle intermetallic compounds at the interface between the coating and the substrate, making it easy to crack under external loads. Ta crystals have a high density, which significantly narrows the path dimension of atomic diffusion. By constructing a high-density Ta as a diffusion barrier on the surface of nickel alloys, not only the spatial constraints during atomic migration are enhanced, but also the energy barrier of diffusion is further increased due to the increase in the lattice distortion effect, making the diffusion process more difficult. Metal coatings usually have lower hardness and higher plasticity, which makes them more susceptible to scratches, wear and deformation when subjected to friction and wear. It can be seen that coating materials with single components and structures and traditional preparation technologies are difficult to simultaneously meet the requirements of wear resistance and corrosion resistance of nickel alloy parts in complex working conditions.

[0035] Due to the synergistic effect of the nanoscale interface effect and the multilayer structure, the comprehensive performance of the nano-multilayer structure coating is usually better than the single-layer system that constitutes its structure. The multilayer alternating structure tends to alleviate the stress concentration of the coating, thereby reducing the risk of cracking and peeling of the coating. In addition, the multilayer alternating structure can interrupt the growth of penetrating columnar crystals and reduce the porosity, thereby improving the corrosion resistance of the coating. In view of the unique heterogeneous interface effect of the multilayer structure, the new material design with material performance 1+1>2 can be achieved by cooperating with the Ta diffusion barrier layer, which can effectively solve the problem of the lack of high-performance micron-thick multifunctional coatings on nickel alloy surfaces in traditional technologies.

[0036] Based on this, the present invention provides a nickel alloy surface composite coating in an embodiment, wherein the composite coating comprises a Ta diffusion barrier layer prepared on the nickel alloy surface and an alternately arranged TiAlTa / (TiAlTa) x C 1-x Functional layer. Ta diffusion barrier layer can effectively alleviate the interdiffusion problem between nickel alloy and coating at high temperature. The alternating TiAlTa / (TiAlTa) x C 1-x The functional layer plays a good role in composition transition, has excellent interlayer bonding, good bonding with the matrix, and has excellent friction reduction, wear resistance and corrosion resistance, allowing the nickel alloy to simultaneously meet complex coupling conditions such as corrosion resistance, fretting wear, and oxidation.

[0037] The high-temperature wear-resistant and corrosion-resistant composite coating on the nickel alloy surface comprises a Ta diffusion barrier layer prepared on the nickel alloy surface and an alternately arranged TiAlTa / (TiAlTa) x C 1-x Functional layer. Reference Figure 1 As shown in FIG. 1 , the Ta diffusion barrier layer 2 is located on the surface of the nickel alloy substrate 1, and the TiAlTa / (TiAlTa) layers are alternately arranged. x C 1-x The functional layer 3 is located on the surface of the Ta diffusion barrier layer 2, TiAlTa / (TiAlTa) x C 1-x The functional layer 3 includes TiAlTa layers and (TiAlTa) layers alternately arranged. x C 1-x layer, and after forming the TiAlTa layer, (TiAlTa) is prepared x C 1-x Layer, TiAlTa / (TiAlTa) x C 1-x The outermost functional layer is (TiAlTa) x C 1-xThe material of the nickel alloy substrate can be any one or more of pure nickel, Inconel 718, Inconel 600, Inconel 750 or Monel 400. The Ta diffusion barrier layer is prepared on the surface of the nickel alloy, and the purity of the Ta diffusion barrier layer is not less than 99%. TiAlTa / (TiAlTa) x C 1-x The TiAlTa layer in the functional layer is composed of the following atomic percentages: Ti40% to 55%, Al30% to 40% and Ta 5% to 25%. This ratio of Ti, Al and Ta is used to improve the oxidation resistance and corrosion resistance of the coating. C, as a strengthening element, forms a ceramic phase with Ti, Al, Ta and other elements to improve the hardness and friction reduction and wear resistance of the coating. Through the reasonable optimization design of the element composition, the corrosion resistance and surface wear resistance of the coating are simultaneously guaranteed. The thickness of the Ta diffusion barrier layer is 200nm to 1000nm.

[0038] TiAlTa / (TiAlTa) x C 1-x The total number of functional layers is 12 to 24 layers, and the TiAlTa layer and (TiAlTa) x C 1-x The modulation ratio of the layers is 1:1 to 1:3, and the outermost layer is (TiAlTa) x C 1-x The modulation ratio is used to represent the deposition time of the TiAlTa layer and (TiAlTa) x C 1-x The ratio of the deposition time of the layers. TiAlTa / (TiAlTa) x C 1-x Functional layer (TiAlTa) x C 1-x The value of x in the layer satisfies 0.3≤x≤0.6. TiAlTa / (TiAlTa) x C 1-x The single layer thickness of the TiAlTa layer in the functional layer is 80-200nm, TiAlTa / (TiAlTa) x C 1-x Functional layer (TiAlTa) x C 1-x The single layer thickness of the layer is 80-400nm, and the total thickness of the composite coating is 2-6μm. The Ta diffusion barrier layer of this thickness can play a role in slow-release nickel alloy substrate and TiAlTa / (TiAlTa) x C 1-xThe interdiffusion of the functional layers avoids the reduction of the hardness of the composite coating caused by the excessive thickness of the Ta diffusion barrier layer, and shortens the deposition cycle. x C 1-x The functional layer forms a good composition transition, which can avoid the interdiffusion between the nickel alloy substrate and the composite coating due to chemical mismatch, resulting in insufficient bonding performance of the coating system.

[0039] TiAlTa / (TiAlTa) x C 1-x Functional layer (TiAlTa) x C 1-x The phases contained include a ceramic phase and an amorphous carbon phase, wherein the ceramic phase can be X a Y b Z c C (X, Y = Ti, Al, Ta, a + b + c = 1) ceramic phase.

[0040] In addition, the present disclosure also provides a method for preparing a nickel alloy surface composite coating, which is used to prepare a nickel alloy surface composite coating. Figure 2 As shown in, the preparation method mainly comprises the following steps:

[0041] In step S210, a TiAl target source and a Ta target source are fixed on a target holder of a vacuum chamber of a magnetron sputtering device, a nickel alloy substrate is placed in the chamber and fixed on a base, and the chamber is evacuated until the vacuum degree reaches a first vacuum degree;

[0042] In step S220, argon gas is introduced into the vacuum chamber and the vacuum degree is maintained at a second vacuum degree, a bias power supply is turned on to perform ion cleaning on the surface of the nickel alloy substrate, and a TiAl target source and a Ta target source are turned on to bombard the nickel alloy substrate to obtain a nickel alloy substrate after bombardment and cleaning;

[0043] In step S230, the flow rate of argon gas is adjusted to maintain the vacuum degree at the second vacuum degree, and a Ta target source is turned on to plate a Ta diffusion barrier layer on the surface of the nickel alloy substrate after bombardment cleaning;

[0044] In step S240, a TiAl target source is turned on to deposit a TiAlTa layer on the surface of the formed Ta diffusion barrier layer;

[0045] In step S250, C is introduced into the vacuum chamber containing the TiAlTa substrate. 2 H 2 / Ar mixed gas, prepared on the surface of TiAlTa layer (TiAlTa) x C 1-x layer;

[0046] In step S260, in (TiAlTa) x C 1-x The surface of the layer is alternately prepared TiAlTa / (TiAlTa) x C 1-x layer, forming a Ta diffusion barrier layer and a TiAlTa / (TiAlTa) x C 1-x Layer of nickel alloy surface composite coating.

[0047] In the embodiment of the present disclosure, for step S210, the distance between the nickel alloy substrate and the TiAl target source and the Ta target source is 50-100 mm, and the first vacuum degree is 5.0×10- 3 ~5.0×10- 4 Pa, the deposition temperature of magnetron sputtering is 250~400℃.

[0048] In step S220, the nickel alloy substrate is bombarded and cleaned. The second vacuum degree can be greater than the first vacuum degree, for example, it can be 0.7 to 1.2 Pa. When the bias power supply is turned on, the negative bias voltage of the bias power supply is -600 to -800 V, and the duty cycle is 60% to 80%; the time for ion cleaning the surface of the nickel alloy substrate is 10 to 25 minutes. When the TiAl target source and the Ta target source are turned on, the arc target power of the TiAl target source and the Ta target source is 100 to 150 W, and the time for bombarding the nickel alloy substrate is 3 to 5 minutes.

[0049] In step S230, a Ta diffusion barrier layer is prepared. Exemplarily, the argon gas flow rate can be adjusted to maintain the vacuum degree at the second vacuum degree. Then only the Ta target source is turned on to plate a Ta diffusion barrier layer on the surface of the nickel alloy substrate after bombardment and cleaning. When plating the Ta diffusion barrier layer, the arc target power can be kept unchanged, that is, the arc target power of the Ta target source is kept unchanged at 100 to 150W. The negative bias voltage of the bias power supply is adjusted to -80 to -120V, the duty cycle is 40% to 60%, the deposition time is 10 to 60min, and a Ta diffusion barrier layer is plated on the surface of the nickel alloy substrate after bombardment and cleaning. The thickness of the Ta diffusion barrier layer is 200 to 1000nm.

[0050] In step S240, a TiAlTa layer is prepared. Exemplarily, the TiAl target source is turned on, and the vacuum degree, arc target power of the Ta target source, negative bias voltage, duty cycle and other conditions are kept unchanged. The arc target power of the TiAl target is set to 100-150W, and the deposition time is 2-5min. A TiAlTa layer is deposited on the surface of the Ta diffusion barrier layer, and the thickness of the TiAlTa layer is 80-200nm. Among them, the vacuum degree is the second vacuum degree, the arc target power of the Ta target source is 100-150W, the negative bias voltage of the bias power supply is -80--120V, and the duty cycle is 40%-60%.

[0051] In step S250, for preparing (TiAlTa) x C 1-x In the vacuum chamber equipped with the TiAlTa layer substrate, the arc target power, negative bias voltage, duty cycle and other conditions are kept the same as those in step S230 and step S240, and then C is introduced into the vacuum chamber. 2 H 2 / Ar mixed gas, and maintain the vacuum degree at the third vacuum degree, the third vacuum degree can be 0.5-1.0Pa, the deposition time is 2-15min, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x Layer, (TiAlTa) x C 1-x The thickness of the layer is 80-400 nm. The arc target power of the Ta target source is 100-150 W, the negative bias voltage of the bias power source is -80--120 V, the duty cycle is 40%-60%, and the arc target power of the TiAl target is set to 100-150 W.

[0052] In step S260, a composite coating is formed. Under the same conditions as those in steps 4 and 5 above, (TiAlTa) x C 1-x The surface of the layer is alternately prepared TiAlTa / (TiAlTa) x C 1-x Functional layer, formed by Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Multi-layer composite coating composed of functional layers.

[0053] In addition, after the composite coating on the surface of the nickel alloy is prepared, the arc source current, gas flow, and heating device can be turned off, and the substrate can be taken out after cooling to room temperature with the furnace to obtain a nickel alloy substrate with a multi-layer composite coating on the surface. The nickel alloy substrate with a multi-layer composite coating on the surface can then be subjected to friction and wear performance tests, 900°C high temperature atmospheric oxidation performance tests, and 95°C concentrated nitric acid (6 mol / L) corrosion performance tests to test its performance.

[0054] Next, the nickel alloy surface composite coating and its preparation method are specifically described in conjunction with embodiments.

[0055] Example 1

[0056] The TiAlTa / (TiAlTa) prepared in this example x C 1-x The total number of functional layers is 12, TiAlTa layer and (TiAlTa) x C 1-xThe modulation ratio of the layers is 1:1.

[0057] The method for preparing the composite coating on the surface of a nickel alloy comprises the following steps:

[0058] Step 1: Fix the TiAl target source and the Ta target source on the target holder of the vacuum chamber of the magnetron sputtering equipment, then load the nickel alloy substrate into the chamber and fix it on the base. The distance between the nickel alloy substrate and the target source is 100 mm, and evacuate the chamber to a vacuum degree of 5.0×10- 3 Pa, the deposition temperature is 250°C; wherein the nickel alloy substrate is Inconel 750 substrate.

[0059] Step 2: introduce argon gas into the vacuum chamber and maintain the vacuum degree at 0.7 Pa, turn on the bias power supply to -600 V, the duty cycle is 80%, and the surface of the nickel alloy substrate is ion cleaned for 25 minutes, and then turn on the TiAl target source and the Ta target source, the arc target power of the TiAl target source and the Ta target source are set to 100 W, and the nickel alloy substrate is bombarded for 5 minutes to obtain the nickel alloy substrate after bombardment and cleaning.

[0060] Step 3: Adjust the argon flow rate to keep the vacuum degree at 0.7Pa, then turn on only the Ta target source, keep the arc target power of the Ta target source unchanged at 100W, adjust the negative bias voltage of the bias power supply to -80V, the duty cycle is 40%, the deposition time is 60min, and a Ta diffusion barrier layer is plated on the surface of the nickel alloy substrate after bombardment and cleaning.

[0061] Step 4: Turn on the TiAl target source, and continue to maintain the same conditions as in step 3, such as vacuum, arc target power of Ta target, negative bias, duty cycle, etc. The arc target power of the TiAl target source is set to 100W, and the deposition time is 2min, and a TiAlTa layer is deposited on the surface of the formed Ta diffusion barrier layer. Among them, the vacuum degree is 0.7Pa, the arc target power of the Ta target source is kept at 100W, and the negative bias of the bias power supply is adjusted to -80V, and the duty cycle is 40%.

[0062] Step 5: In the vacuum chamber equipped with the TiAlTa substrate, keep the arc target power, negative bias voltage, duty cycle and other conditions the same as those in Steps 3 and 4. Then, introduce C 2 H 2 / Ar mixed gas, and maintain the vacuum degree at 0.5Pa, the deposition time is 2min, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x The arc target power of the Ta target source and the arc target power of the TiAl target source are kept unchanged at 100W, and the negative bias voltage of the bias power supply is adjusted to -80V, with a duty cycle of 40%.

[0063] Step 6: Under the same conditions as Step 4 and Step 5 above, (TiAlTa) x C 1-x Five cycles of TiAlTa / (TiAlTa) are deposited on the surface of the layer. x C 1-x Functional layer, formed by Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Multi-layer composite coating composed of functional layers.

[0064] Step 7: Turn off the arc source current, gas flow, heating device, etc., cool the furnace to room temperature and then take it out to obtain an Inconel 750 substrate with a wear-resistant and corrosion-resistant coating on the surface.

[0065] After testing, the Inconel 750 substrate with a composite coating deposited on the surface prepared in this embodiment has a TiAlTa layer composed of the following atomic percentages: Ti: 47.7%, Al: 38.2% and Ta: 14.1%, (TiAlTa) x C 1-x The thickness of the Ta diffusion barrier layer is about 1.0 μm, TiAlTa / (TiAlTa) x C 1-x The total thickness of the functional layer is 1.1 μm, and the total thickness of the composite coating is 2.1 μm. The Inconel 750 substrate with the composite coating deposited on the surface was sampled for friction and wear performance, 900°C high temperature atmospheric oxidation performance and 95°C concentrated nitric acid (6 mol / L) corrosion performance tests. The wear rate was 4.3×10- 6 mm 3 / (N·m), weight gain after 800℃ high temperature atmospheric oxidation for 3h is 6.2mg / cm 2 , the self-corrosion potential is 0.55V, so it has excellent wear resistance and corrosion resistance.

[0066] Example 2

[0067] The TiAlTa / (TiAlTa) prepared in this example x C 1-x The total number of functional layers is 18, TiAlTa layer and (TiAlTa) x C 1-x The modulation ratio of the layer is 1:3.

[0068] The method for preparing the composite coating on the surface of a nickel alloy comprises the following steps:

[0069] Step 1: Fix the TiAl target source and Ta target source on the target holder of the vacuum chamber of the magnetron sputtering equipment, then load the Inconel 600 substrate into the chamber and fix it on the base. The distance between the substrate and the target is 50 mm. Evacuate the chamber to a vacuum degree of 1.0×10- 3 Pa, the deposition temperature is 300°C; wherein the nickel alloy substrate is an Inconel 600 substrate.

[0070] Step 2, introducing argon gas into the vacuum chamber and maintaining the vacuum degree at 0.9 Pa, turning on the bias power supply to -700 V, with a duty cycle of 70%, ion cleaning the surface of the nickel alloy substrate for 15 minutes, and then turning on the TiAl target source and the Ta target source, setting the arc target power to 120 W, bombarding the nickel alloy substrate for 4 minutes, and obtaining a nickel alloy substrate after bombardment and cleaning;

[0071] Step 3: Adjust the argon flow rate to maintain the vacuum degree at 0.9 Pa, then turn on only the Ta target source, keep the arc target power of the Ta target source unchanged at 120 W, adjust the negative bias voltage of the bias power supply to -100 V, the duty cycle is 50%, the deposition time is 30 min, and a Ta diffusion barrier layer is plated on the surface of the nickel alloy substrate after bombardment and cleaning.

[0072] Step 4: Turn on the TiAl target source, and continue to keep the vacuum, Ta target arc power, negative bias, duty cycle and other conditions unchanged. The arc power of the TiAl target source is set to 120W, and the deposition time is 5min. The TiAlTa layer is deposited on the surface of the Ta diffusion barrier layer. Among them, the vacuum degree is 0.9Pa, the arc power of the Ta target source is kept at 120W, and the negative bias of the bias power supply is adjusted to -100V, and the duty cycle is 50%.

[0073] Step 5: In a vacuum chamber containing the obtained TiAlTa layer substrate, keep the arc target power, negative bias voltage, duty cycle and other conditions unchanged, and then introduce C into the vacuum chamber. 2 H 2 / Ar mixed gas, and maintain the vacuum degree at 0.7Pa, the deposition time is 15min, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x The arc target power of the Ta target source and the TiAl target source is kept unchanged at 120W, and the negative bias voltage of the bias power supply is adjusted to -100V, with a duty cycle of 50%.

[0074] Step 6: Under the same conditions as in Step 4 and Step 5 above, x C 1-x 8 cycles of TiAlTa / (TiAlTa) are deposited on the surface of the layer x C 1-xFunctional layer, formed by Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Multi-layer composite coating composed of functional layers.

[0075] Step 7: Turn off the arc source current, gas flow, heating device, etc., cool the furnace to room temperature and then take it out to obtain an Inconel 600 substrate with a wear-resistant and corrosion-resistant coating on the surface.

[0076] After testing, the Inconel 600 substrate with a composite coating deposited on the surface prepared in this embodiment has a TiAlTa layer composed of the following atomic percentages: Ti: 47.3%, Al: 40.9% and Ta: 11.8%, (TiAlTa) x C 1-x The thickness of the Ta diffusion barrier layer is 600nm, TiAlTa / (TiAlTa) x C 1-x The total thickness of the functional layer is 5.1 μm, and the total thickness of the composite coating is 5.7 μm. The Inconel 600 substrate with the composite coating deposited on the surface was sampled for friction and wear performance, 900°C high temperature atmospheric oxidation performance and 95°C concentrated nitric acid (6 mol / L) corrosion performance tests. The wear rate was 5.7×10- 7 mm 3 / (N·m), reference Figure 4 As shown in the figure, it can be seen that the wear rate is low. The weight increase after 800℃ high temperature atmospheric oxidation for 3h is 4.1mg / cm 2 , the self-corrosion potential is 0.63 V. Therefore, it has excellent wear resistance and corrosion resistance.

[0077] Example 3

[0078] The TiAlTa / (TiAlTa) prepared in this example x C 1-x The total number of functional layers is 24, TiAlTa layer and (TiAlTa) x C 1-x The modulation ratio of the layer is 1:2.

[0079] The method for preparing the composite coating on the surface of a nickel alloy comprises the following steps:

[0080] Step 1: Fix the TiAl target source and Ta target source on the target holder of the vacuum chamber of the magnetron sputtering equipment, then load the pure nickel substrate into the chamber and fix it on the base. The distance between the substrate and the target source is 70 mm. Evacuate the chamber to a vacuum degree of 8.0×10- 4 Pa, and the deposition temperature is 350 °C.

[0081] Step 2: introduce argon gas into the vacuum chamber and maintain the vacuum degree at 1.0 Pa, turn on the bias power supply to a negative bias voltage of -800 V, a duty cycle of 60%, perform ion cleaning on the substrate surface for 10 minutes, and then turn on the TiAl target source and the Ta target source. The arc target power of the TiAl target source and the Ta target source is set to 150 W, and the substrate is bombarded for 5 minutes to obtain a substrate after bombardment and cleaning.

[0082] Step 3: Adjust the argon flow rate to maintain the vacuum degree at 1.0Pa, then turn on only the Ta target source, keep the arc target power of the Ta target source unchanged, adjust the negative bias voltage of the bias power supply to -120V, the duty cycle is 60%, the deposition time is 10min, and a Ta diffusion barrier layer is plated on the substrate surface.

[0083] Step 4: Turn on the TiAl target source, and continue to maintain the same vacuum, arc target power of the Ta target source, negative bias, duty cycle and other conditions as in step 3. The arc target power of the TiAl target source is set to 100W, the deposition time is 3min, and a TiAlTa layer is deposited on the surface of the formed Ta diffusion barrier layer. Among them, the vacuum degree is 1.0Pa, the arc target power of the Ta target source is kept at 150W, the negative bias of the bias power supply is adjusted to -120V, and the duty cycle is 60%.

[0084] Step 5: In a vacuum chamber containing the obtained TiAlTa layer substrate, keep the arc target power, negative bias voltage, duty cycle and other conditions unchanged, and then introduce C into the vacuum chamber. 2 H 2 / Ar mixed gas, and maintain the vacuum degree at 1.0Pa, the deposition time is 6min, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x The arc target power of the Ta target source is kept at 150W, the arc target power of the TiAl target source is kept at 100W, and the negative bias voltage of the bias power supply is adjusted to -120V, with a duty cycle of 60%.

[0085] Step 6: Under the same conditions as in Step 4 and Step 5 above, x C 1-x 11 cycles of TiAlTa / (TiAlTa) are deposited on the surface of the layer x C 1-x Functional layer, formed by Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Multi-layer composite coating composed of functional layers.

[0086] Step 7: turn off the arc source current, gas flow, heating device, etc., cool down to room temperature with the furnace and then take it out to obtain a pure nickel substrate with a wear-resistant and corrosion-resistant coating on the surface.

[0087] After testing, the pure nickel substrate with a composite coating deposited on the surface prepared in this embodiment has a TiAlTa layer composed of the following atomic percentages: Ti: 40.8%, Cr: 32.7% and Ta: 22.5%. (TiAlTa) x C 1-x The thickness of the Ta diffusion barrier layer is 200nm, TiAlTa / (TiAlTa) x C 1-x The total thickness of the functional layer is 3.9 μm, and the total thickness of the composite coating is 4.1 μm.

[0088] The pure nickel substrate with composite coating deposited on the surface was sampled for friction and wear performance, 900℃ high temperature atmospheric oxidation performance and 95℃ concentrated nitric acid (6mol / L) corrosion performance test. It was found that the wear rate was 1.2×10- 6 mm 3 / (N·m), weight gain after 800℃ high temperature atmospheric oxidation for 3h is 3.6mg / cm 2 , the self-corrosion potential is 0.63V. Figure 5 It can be seen that the composite coating is intact after being oxidized at 800℃ for 3h; Figure 6 It can be seen that the composite coating did not fall off after being oxidized at 800℃ for 3h. Therefore, it has excellent wear resistance and corrosion resistance, and the effect is good.

[0089] Example 4

[0090] The TiAlTa / (TiAlTa) prepared in this example x C 1-x The total number of functional layers is 20, TiAlTa layer and (TiAlTa) x C 1-x The modulation ratio of the layers is 1:1.

[0091] The method for preparing the composite coating on the surface of a nickel alloy comprises the following steps:

[0092] Step 1: Fix the TiAl target source and Ta target source on the target holder of the vacuum chamber of the magnetron sputtering equipment, then load the Inconel 718 substrate into the chamber and fix it on the base. The distance between the substrate and the target source is 80 mm. Evacuate the chamber to a vacuum degree of 5.0×10- 4 Pa, and the deposition temperature is 400 °C.

[0093] Step 2: introduce argon gas into the vacuum chamber and maintain the vacuum degree at 1.2 Pa, turn on the bias power supply to -750 V, the duty cycle is 65%, and the substrate surface is ion cleaned for 20 minutes, and then turn on the TiAl target source and the Ta target source. The arc target power of the TiAl target source and the Ta target source is 100 W, and the substrate is bombarded for 4 minutes to obtain a nickel alloy substrate after bombardment and cleaning.

[0094] Step 3: Adjust the argon gas flow rate to maintain the vacuum degree at 1.2Pa, then turn on only the Ta target source, keep the arc target power of the Ta target source unchanged at 100W, adjust the negative bias voltage of the bias power supply to -110V, the duty cycle is 55%, the deposition time is 20min, and a Ta diffusion barrier layer is plated on the surface of the nickel alloy substrate after bombardment and cleaning.

[0095] Step 4, turn on the TiAl target source, and continue to keep the vacuum degree, arc target power of the Ta target source, negative bias, duty cycle and other conditions unchanged, the arc target power of the TiAl target source is set to 130W, the deposition time is 4min, and the surface of the Ta diffusion barrier layer formed in step 4 is deposited to form a TiAlTa single layer. Among them, the vacuum degree is 1.2Pa, the arc target power of the Ta target source is 100W, the negative bias of the bias power supply is adjusted to -110V, and the duty cycle is 55%.

[0096] Step 5: In a vacuum chamber containing the obtained TiAlTa layer substrate, keep the arc target power, negative bias voltage, duty cycle and other conditions unchanged, and then introduce C into the vacuum chamber. 2 H 2 / Ar mixed gas, and maintain the vacuum degree at 1.2Pa, the deposition time is 4min, and (TiAlTa) is prepared on the surface of the TiAlTa layer x C 1-x The arc target power of the Ta target source is 100W, the arc target power of the TiAl target source is 130W, the negative bias voltage of the bias power supply is adjusted to -110V, and the duty cycle is 55%.

[0097] Step 6: Under the same conditions as in Step 4 and Step 5, x C 1-x The surface of the layer is deposited with 9 cycles of TiAlTa / (TiAlTa) x C 1-x Functional layer, formed by Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Multi-layer composite coating composed of functional layers.

[0098] Step 7: Turn off the arc source current, gas flow, heating device, etc., cool the furnace to room temperature and then take it out to obtain an Inconel 718 substrate with a wear-resistant and corrosion-resistant coating on the surface.

[0099] After testing, the Inconel 718 substrate with a composite coating deposited on the surface prepared in this embodiment has a TiAlTa layer composed of the following atomic percentages: Ti: 54.8%, Cr: 39.3% and Ta: 5.9%. (TiAlTa) x C 1-x x≈0.56 in the layer; the thickness of the Ta diffusion barrier layer is 400nm, TiAlTa / (TiAlTa) x C 1-x The total thickness of the functional layer is 3.5 μm, and the total thickness of the composite coating is 3.9 μm. The Inconel 718 substrate with the composite coating deposited on the surface was sampled for friction and wear performance, 900°C high temperature atmospheric oxidation performance and 95°C concentrated nitric acid (6 mol / L) corrosion performance tests. The wear rate was 2.4×10 -6 mm 3 / (N·m), weight gain after 800℃ high temperature atmospheric oxidation for 3h is 5.2mg / cm 2 . refer to Figure 7 As shown in , the self-corrosion potential is 0.61V, so it has excellent wear resistance and corrosion resistance, and the effect is good.

[0100] In summary, the present disclosure adopts Ta as a diffusion barrier layer, which not only provides excellent corrosion resistance and can effectively resist the erosion of various corrosive media including strong acids and strong alkalis, but also significantly reduces the mutual diffusion effect of elements such as Ti and Al in the nickel alloy and the coating under high temperature conditions, effectively avoiding the problem of brittle intermetallic compounds that are easily generated at the interface between traditional Cr and Ti-based coatings and Ni substrates, and significantly enhances the bonding force between the coating and the substrate. By alternately setting TiAlTa / (TiAlTa) x C 1-x Functional layer, the multi-layer alternating structure formed can interrupt the growth of penetrating columnar crystals, reduce porosity, and thus improve the corrosion resistance of the composite coating. x C 1-x The inclusion of various MAX phases and carbide phases also provides the coating with good friction reduction and wear resistance. In the embodiment of the present disclosure, by precisely controlling the TiAlTa / (TiAlTa) x C 1-x The elemental composition ratio of the functional layer, combined with the modulation period design and preparation process optimization of the functional layer, effectively inhibited the continuous growth of columnar crystals, and successfully prepared a highly dense near-equiaxed crystal structure coating, which effectively prevented the rapid diffusion of corrosive media along the grain boundaries, thereby improving its corrosion resistance.

[0101] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0102] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0103] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A composite coating on a nickel alloy surface, characterized in that: The nickel alloy surface composite coating comprises a Ta diffusion barrier layer prepared on the nickel alloy surface, and TiAlTa / (TiAlTa) alternately arranged on the surface of the Ta diffusion barrier layer. x C 1-x Functional layer.

2. The nickel alloy surface composite coating according to claim 1, characterized in that: TiAlTa / (TiAlTa) x C 1-x The total number of functional layers is 12 to 24 layers, and the TiAlTa / (TiAlTa) x C 1-x TiAlTa layer in the functional layer and (TiAlTa) x C 1-x The modulation ratio of the layer is 1:1 to 1:3, and the TiAlTa / (TiAlTa) x C 1-x The outermost layer of the functional layer is (TiAlTa) x C 1-x The total thickness of the composite coating is 2 to 6 μm.

3. The nickel alloy surface composite coating according to claim 1, characterized in that: The purity of the Ta diffusion barrier layer is not less than 99%, and the thickness of the Ta diffusion barrier layer is 200-1000 nm.

4. The nickel alloy surface composite coating according to claim 1, characterized in that: TiAlTa / (TiAlTa) x C 1-x The single layer thickness of the TiAlTa layer in the functional layer is 80-200nm; the TiAlTa layer is composed of the following components in atomic percentage: 40%-55% Ti, 30%-40% Al and 5%-25% Ta.

5. The nickel alloy surface composite coating according to claim 1, characterized in that: (TiAlTa) x C 1-x In the layer, x satisfies 0.3≤x≤0.6, and the (TiAlTa) x C 1-x The single layer thickness of the layer is 80 to 400 nm, and the (TiAlTa) x C 1-x The phases contained in the layer include a ceramic phase and an amorphous carbon phase; the ceramic phase is X a Y b Z c C (X, Y, Z = Ti, Al, Ta, a + b + c = 1) ceramic phase.

6. A method for preparing a composite coating on a nickel alloy surface, for preparing the composite coating on a nickel alloy surface as claimed in any one of claims 1 to 5, characterized in that: include: Fixing a TiAl target source and a Ta target source on a target holder of a vacuum chamber of a magnetron sputtering device, placing a nickel alloy substrate into the chamber and fixing it on a base, and evacuating the chamber until the vacuum degree reaches a first vacuum degree; Argon gas is introduced into the vacuum chamber and the vacuum degree is maintained at a second vacuum degree, a bias power supply is turned on to perform ion cleaning on the surface of the nickel alloy substrate, and a TiAl target source and a Ta target source are turned on to bombard the nickel alloy substrate to obtain a nickel alloy substrate after bombardment and cleaning; The flow rate of argon gas is adjusted to maintain the vacuum degree at the second vacuum degree, and a Ta target source is turned on to plate a Ta diffusion barrier layer on the surface of the nickel alloy substrate after bombardment cleaning; Turning on the TiAl target source to deposit a TiAlTa layer on the surface of the formed Ta diffusion barrier layer; In a vacuum chamber equipped with a TiAlTa layer substrate, a C2H2 / Ar mixed gas is introduced into the vacuum chamber to prepare (TiAlTa) on the surface of the TiAlTa layer. x C 1-x layer; In (TiAlTa) x C 1-x The surface of the layer is alternately prepared TiAlTa / (TiAlTa) x C 1-x Functional layer, including Ta diffusion barrier layer and TiAlTa / (TiAlTa) x C 1-x Composite coating on nickel alloy surface with functional layer.

7. The method for preparing a composite coating on a nickel alloy surface according to claim 6, characterized in that: The distance between the nickel alloy substrate and the TiAl target source and the Ta target source is 50-100 mm, and the first vacuum degree is 5.0×10 -3 ~5.0×10 -4 Pa, the deposition temperature of magnetron sputtering is 250~400℃.

8. The method for preparing a composite coating on a nickel alloy surface according to claim 6, characterized in that: In the step of ion cleaning, the negative bias voltage of the bias power supply is -600 to -800 V, and the duty cycle is 60% to 80%; the ion cleaning time is 10 to 25 minutes, the arc target power of the TiAl target source and the Ta target source is 100 to 150 W, and the bombardment time is 3 to 5 minutes.

9. The method for preparing a composite coating on a nickel alloy surface according to claim 6, characterized in that: When the Ta target source is turned on, the arc target power of the Ta target source is 100-150W, the negative bias voltage of the bias power supply is -80--120V, the duty cycle is 40%-60%, the deposition time is 10-60min, and the thickness of the Ta diffusion barrier layer is 200-1000nm; when the TiAl target source is turned on, the vacuum degree, the arc target power, the negative bias voltage, and the duty cycle of the Ta target source are the same as those when the Ta target source is turned on, the arc target power of the TiAl target source is 100-150W, and the deposition time is 2-5min.

10. The method for preparing a composite coating on a nickel alloy surface according to claim 6, characterized in that: In the vacuum chamber equipped with the TiAlTa layer substrate, C2H2 / Ar mixed gas is introduced into the vacuum chamber to prepare (TiAlTa) on the surface of the TiAlTa layer. x C 1-x Layers, including: Keeping the arc target power, negative bias voltage and duty cycle of the TiAl target source and the Ta target source unchanged, introducing C2H2 / Ar mixed gas into the vacuum chamber, and maintaining the vacuum degree at the third vacuum degree, the deposition time is 2 to 15 minutes, and (TiAlTa) is prepared on the surface of the TiAlTa layer. x C 1-x layer.

Citation Information

Cited By

  • Tantalum-based multilayer composite powder, preparation method thereof and cold spraying coating material

    CN120362484A